Evaluation of bone surface registration applying a microneedle array - Kurt Schicho (Blackwell Synergy, 2007)
Aim: In this study we present and evaluated a new registration technology for the jaw-bone surface. It is based on a micromechatronic device for the generation of a ‘‘mechanical image’’ of the bone surface by means of an array of micro-needles that are penetrating the soft tissue until they touch the surface of the bone. This ‘‘mechanical impression image’’ is aligned with the CT data set. Material and Methods: Based on laboratory measurements on 10 specially prepared jawbone models we evaluate the accuracy of this new registration method. Results: Our measurements of the 10 specimens revealed a maximum overall location error of 0.97mm (range: 0.35–0.97 mm). Conclusions: From the technical point of view the presented registration technology has the potential to improve the performance (i.e. accuracy and avoidance of errors) of the registration process for bony structures in selected applications of image-guided surgery.